Reinstatement and redescription of Forsterinaria inornata magdalena (Hayward) (Nymphalidae: Satyrinae) from Cochabamba, Bolivia - Zubek, Anna; Pyrcz, Tomasz W. (Zootaxa, 2015)
Taxonomic status of Forsterinaria inornata magdalena (Hayward, 1957) from Cochabamba, Bolivia is revised, and a detailed redescription of adult male morphology, including the genitalia is presented.